2001
DOI: 10.1074/jbc.m008128200
|View full text |Cite
|
Sign up to set email alerts
|

Amyloid-β Interactions with Chondroitin Sulfate-derived Monosaccharides and Disaccharides

Abstract: In Alzheimer's disease, the major pathological features are diffuse and senile plaques that are primarily composed of the amyloid-␤ (A␤) peptide. It has been proposed that proteoglycans and glycosaminoglycans (GAG) facilitate amyloid fibril formation and/or stabilize the plaque aggregates. To develop effective therapeutics based on A␤-GAG interactions, understanding the A␤ binding motif on the GAG chain is imperative. Using electron microscopy, fluorescence spectroscopy, and competitive inhibition ELISAs, we h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
46
2

Year Published

2002
2002
2017
2017

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 77 publications
(53 citation statements)
references
References 39 publications
5
46
2
Order By: Relevance
“…In agreement with this view we have shown that sulfated polymeric GAGs are efficient promoters of A␤ fibril formation. Other studies (62) have shown that CSB-derived monosaccharides represent the minimal GAG subunit required for A␤ binding and that lateral aggregation between A␤ fibrils or the transition of protofilaments into mature amyloid fibrils requires at least a sulfated GAG disaccharide, with the disulfated derivative being the most effective. These results suggest that subtle changes in the GAG backbone and distribution of sulfation have significant effects on the ability of chondroitin sulfate to organize A␤ into amyloid fibrils.…”
Section: Discussionmentioning
confidence: 99%
“…In agreement with this view we have shown that sulfated polymeric GAGs are efficient promoters of A␤ fibril formation. Other studies (62) have shown that CSB-derived monosaccharides represent the minimal GAG subunit required for A␤ binding and that lateral aggregation between A␤ fibrils or the transition of protofilaments into mature amyloid fibrils requires at least a sulfated GAG disaccharide, with the disulfated derivative being the most effective. These results suggest that subtle changes in the GAG backbone and distribution of sulfation have significant effects on the ability of chondroitin sulfate to organize A␤ into amyloid fibrils.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, inhibition of cerebral A␤ aggregation is an important goal in AD therapy. Several compounds have been reported to have such an effect: melatonin (24), some nonsteroidal antiinflammatory drugs (25), sulfated mono-and disaccharides (26), synthetic peptides (27,28), and cerebrospinal-fluid proteins such as thransthyretin (29). Because of the known relationship between oxidative stress and AD and because of the established antioxidative properties of Ginkgo biloba, it has been proposed that EGb761 exerts its neuroprotective effects mostly as an intracellular antioxidant (1).…”
Section: Discussionmentioning
confidence: 99%
“…These notions suggest the possibility that exogenous GAGs or related polyanionic molecules may competitively bind to Ab and thus influence Ab fibrillation (2,6,7). Current views hold that some exogenous LMW heparin or LMW chondroitin sulfate possesses dramatic binding ability for Ab , subsequently leading to suppression of fibril aggregation (12,17). AOSC is structurally rich in 1,4-linked b-D-mannuronate with highly negatively charged residues, permitting its high affinity for Ab.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, compounds that can interfere with the interaction between endogenous GAGs and Ab may prevent the formation of SPs. Recent studies both in vivo and in vitro have suggested that lowmolecular-weight (LMW) GAGs such as LMW heparin or LMW chondroitin sulfate might ameliorate the cytotoxic effect of Ab and prevent the amyloid deposit through binding to Ab to interfere with its fibril formation (12,16,17). These findings suggested that LMW GAGs derivatives and their analogues may possess possible therapeutical potentials for AD.…”
Section: Introductionmentioning
confidence: 94%